(±)-Spiroganoapplanin A, a complex polycyclic meroterpenoid dimer from Ganoderma applanatum displaying potential against Alzheimer's disease. Issue 11 (4th May 2022) - Peng, Xing-Rong; Luo, Rong-Can; Su, Hai-Guo; Zhou, Lin; Ran, Xiao-Qian; Guo, Ya-Rong; Yao, Yong-Gang; Qiu, Ming-Hua
Abstract : (±)-spiroganoapplanin A (1 ) with a polycyclic meroterpenoid from  Ganoderma applanatum  showed potential anti-AD's effect by reducing Aβ42 production and inhibiting Tau phosphorylation through BACE1, CDK5, and GSK3β-mediated pathways. Abstract : (±)-Spiroganoapplanin A (1 ) representing a new subtype of the Ganoderma meroterpenoid dimer with a 6/5/5/6/5/6 hexacyclic system was isolated from Ganoderma applanatum . Using spectroscopic, X-ray crystallographic and electronic circular dichroism analyses, the structure of the racemic natural product was determined, and its unusual NMR behavior was investigated by variable-temperature NMR experiments. The possible biogenetic pathway for 1 was proposed. Cellular assays showed that (±)-1, (+)-1, and (−)-1 all reduce Aβ42 production and inhibit tau phosphorylation through BACE1, CDK5, and GSK3β-mediated pathways, suggesting their potential against Alzheimer's disease.